Pertanggungjawaban Notaris terhadap Akta Perjanjian Utang Piutang: Putusan Nomor 5/Pdt.G/2023/PN Btl - maria komala (Jurnal Hukum Lex Generalis, 2025)
Notaries as public officials have the authority to make authentic deeds that provide legal certainty for society. This research analyzes notary liability in Decision Number 5/Pdt.G/2023/PN Btl where the notary made intentional errors in making debt and receivables agreement deeds. The research method uses a normative juridical approach with case analysis. Results show that the notary violated Article 16 paragraph (1) letters a and m of the Notary Position Law by making deeds that harmed one party. Consequently, the deed degraded to an under-hand deed. The notary was subject to administrative sanctions and potentially faced civil compensation claims.